Novel composite positive electrode material of secondary battery and preparation method of novel composite positive electrode material
By combining bismuth ferrate with traditional positive electrode materials, composite positive electrode materials with ferroelectricity and piezoelectric properties are prepared, which solves the problem of insufficient electrochemical performance of existing positive electrode materials and achieves higher energy density and longer Cycle life and better rate performance.
Patent Information
- Application Number
- CN202411177089.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-26
- Publication Date
- 2025-02-18
AI Technical Summary
The electrochemical performance of existing secondary battery positive electrode materials is insufficient, resulting in low energy density, poor cycle stability, poor rate performance and severe voltage attenuation, making it difficult to meet the growing market demand.
Bismuth ferrate is introduced as a reinforced phase, combined with traditional positive electrode materials, and prepared bismuth ferrate modified positive electrode materials through sol-gel method, co-precipitation method and other methods to form composite materials with ferroelectricity and piezoelectric properties, and adjust the materials The distribution state of charge in the process increases the Li+ migration rate.
The discharge specific capacity, Coulomb efficiency, cycle stability, rate performance and voltage attenuation of the positive electrode material are significantly improved, delaying the rapid decay of the material performance and improving the overall electrochemical performance of the battery.
Smart Images

Figure CN119480944A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of secondary battery positive electrode materials, and in particular relates to a novel composite positive electrode material for a secondary battery and a preparation method thereof. Background Art
[0002] The continuous growth of population and the depletion of fossil fuels have triggered a huge demand for alternative energy production, storage and distribution systems. In the field of energy storage, rechargeable / secondary batteries are the most energy-efficient storage devices because they can convert electrical energy into chemical energy and release it when needed. At present, secondary battery technologies mainly include lead-acid, nickel-metal hydride (Ni-MH), lithium-ion batteries (LIB) and sodium-ion batteries (SIB). Among them, lithium-ion batteries have rapidly become popular due to their high energy density and are widely used in various industries, especially consumer electronics, hybrid and pure electric vehicles (HEV and EV), etc. Sodium-ion batteries have attracted widespread attention from a large number of researchers due to their advantages such as abundant resources, low cost and high energy density. At present, the demand for secondary batteries in the market shows an explosive growth trend.
[0003] Secondary batteries are usually mainly composed of positive and negative electrode materials, electrolytes, and isolation materials. In the entire battery system, the positive electrode material is the most important part of the battery and is also the key to further improving the battery energy density. The specific capacity of commonly used positive electrode materials such as lithium cobalt oxide, lithium iron phosphate, lithium manganese oxide, lithium nickel oxide, ternary nickel cobalt manganese oxide, and lithium-rich manganese-based positive electrode materials with high specific capacity is much lower than that of commonly used negative electrode materials such as graphite (372 mAh g -1 ), so it is particularly important to develop positive electrode materials with higher energy density. The capacity of positive electrode materials mainly depends on the type of materials, but the original positive electrode materials are usually accompanied by poor electrochemical performance, such as low coulombic efficiency, poor cycle stability, poor rate performance, and severe voltage decay. At present, the performance of positive electrode materials can be further improved through certain means of modification, so that the battery has a higher energy density and a longer service life, better meeting people's needs.
[0004] In response to the above problems, a large number of scientific researchers have carried out research on battery positive electrode materials, using various modification strategies to improve the electrochemical properties of positive electrode materials, among which doping, coating, morphology control, and material surface treatment are relatively commonly used modification strategies.
[0005] Element doping (cation / anion / cation co-doping) can improve the intrinsic conductivity and ion diffusion rate of the material and construct a stable surface heterogeneous interface, thereby improving the electrochemical performance of the material. However, the amount of doping needs to be precisely controlled, and it may introduce additional chemical reactions and changes in electrochemical activity, affecting the battery capacity and cycle life. For example, Sun et al. first synthesized LiNiO by the sol-gel method using adipic acid as a chelating agent. 2 The precursor was then doped with sulfur powder by solid phase reaction in an oxygen flowing atmosphere to prepare LiNiS y O 2-y Compounds. Studies have shown that LiNiS y O 2-y The capacity retention of the material is significantly improved, but its initial discharge capacity is lower than that of unmodified LiNiO 2 material, and the capacity gradually decreases with the increase of sulfur content.
[0006] Coating modification (electrochemical inertness / fast ion conductor / SEI film coating) can avoid direct contact between active materials and electrolytes, prevent electrolyte corrosion on the material surface and the occurrence of interface side reactions, improve the ion and electronic conductivity of the material and enhance the performance of the positive electrode material, but it will also cause problems such as decreased material capacity and side reactions at the interface between the coating layer and the positive electrode material. For example, patent CN109509874A discloses a method for preparing a lithium-rich manganese-based positive electrode material coated with molybdenum trioxide, which is obtained by wet mixing the lithium-rich manganese-based material with ammonium molybdate, evaporating it in a water bath, and then heat treating it at high temperature to obtain a modified lithium-rich manganese-based material. Although the oxide coating obtained by this method can improve the cycle stability, it does not effectively eliminate the residual lithium on the surface of the material, and has limited inhibitory effect on the side reactions on the electrode surface. Moreover, molybdenum trioxide, as an inert coating, often hinders the charge transfer of the electrode material and reduces the mass energy density of the electrode active material, so it has certain limitations in application.
[0007] Special microstructure regulation (constructing core-shell structure / full concentration gradient structure / micro-nanostructure design / special crystal surface design, etc.) can improve the surface structure stability of the material, improve the ionic conductivity and electronic conductivity of the material, and thus enhance the electrochemical performance of the material. However, it requires in-depth material design and synthesis work, is costly, and may not necessarily significantly improve performance. Zhang et al. introduced the core-shell structure into the field of positive electrode materials and used LiNiO for the first time. 2 -LiCoO 2 -LiMnO 2 A special double-shell high-nickel ternary material was designed and synthesized using a triangular phase diagram. Its core LiNi 0.8 Co 0.1 Mn 0.1 It can provide high reversible capacity, while the inner shell LiNi 1 / 3 Co1 / 3 Mn 1 / 3 O 2 and shell LiNi 0.4 Co 0.2 Mn 0.4 O 2 They showed excellent rate performance and structural stability respectively. However, subsequent studies found that the core-shell layered cathode material had structural mismatch after long cycles, that is, a gap layer of tens of nanometers appeared between the core and the shell, which seriously hindered the Li + migration and electron transfer, resulting in a rapid decrease in electrochemical performance.
[0008] Chemical treatment (acid treatment, reducing agent / oxidizing agent treatment, ammonium salt treatment, etc.) can improve structural stability and regulate surface chemical properties by constructing a stable surface coherent heterostructure interface to minimize side reactions and prevent harmful volume changes. However, its operation cost is high, the conditions are difficult to control, and the reproducibility is poor, making it difficult to apply to actual production. Wang et al. reported a novel and reasonable strategy to simultaneously regulate the surface structure and chemical composition of lithium-rich oxide particles. They used an appropriate concentration of NH 3 ·H 2 O-treated spherical Mn 0.6 Co 0.2 Ni 0.2 CO 3 precursor, and make full use of Ni 2+ Ion and NH 3 ·H 2 O obtains an intermediate with a nickel-poor feature on the surface, and after sintering, a phase gradient layer with a "layered@spinel" structure is formed on the outer surface of the material. The spinel structure with three-dimensional channels is conducive to Li + The rapid migration of ions can stabilize the surface structure; the compatible gradient structure layer will reduce the charge transfer resistance and further improve the electrochemical performance of the material. In addition, the chemical properties of the surface nickel deficiency can further improve the stability of the positive electrode material. Thanks to the synergistic effect of the above multiple functions, the electrochemical performance of the modified material has been significantly improved.
[0009] By modifying the positive electrode material, the electrochemical performance of the material can be improved to a certain extent. However, it is difficult for a single modification method to improve battery performance in all aspects. Although combined modification can improve electrochemical performance to a greater extent, there are also some problems that need to be solved. For example, the difficulty of achieving synergy, cost, potential side reactions, etc. Therefore, how to simply and effectively improve the electrochemical properties of positive electrode materials (discharge capacity, coulombic efficiency, cycle stability, rate performance, voltage attenuation, etc.) is a thorny problem and a common goal of a wide range of researchers.
[0010] In view of the shortcomings of the prior art, the present invention provides a method for enhancing the electrochemical performance of the positive electrode material of a secondary battery by using bismuth ferrite as an auxiliary. Bismuth ferrite is introduced into the positive electrode material for the first time, which greatly improves its electrochemical performance. On the one hand, the presence of bismuth ferrite can effectively reduce the side reaction between the bulk positive electrode material and the electrolyte, prevent the dissolution of transition metals, reduce the polarization phenomenon of the material during the electrochemical reaction, and slow down the rapid decline of the performance of the positive electrode material; on the other hand, bismuth ferrite has ferroelectricity and piezoelectric properties. The unique spontaneous polarization and piezoelectric effect properties can adjust the distribution state of the charge in the material, forming an active "acceleration channel" during the battery charging and discharging process, improving Li + The migration rate can effectively promote the insertion and extraction process of lithium ions, further improving the electrochemical performance of the battery. Summary of the invention
[0011] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a new composite positive electrode material for a secondary battery and a preparation method thereof, which can greatly and comprehensively improve the electrochemical performance of the battery. With a traditional positive electrode material as the matrix phase and bismuth ferrite as the reinforcing phase; combining bismuth ferrite with the traditional positive electrode material, a new composite positive electrode material with greatly improved electrochemical performance can be obtained. The introduction of bismuth ferrite into the positive electrode material can effectively reduce the side reactions between the bulk material and the electrolyte, prevent the dissolution of transition metals, reduce the polarization phenomenon during the electrochemical reaction, and delay the rapid decline of the performance of the positive electrode material. At the same time, bismuth ferrite has ferroelectric and piezoelectric properties. The unique spontaneous polarization and piezoelectric effect properties can adjust the distribution state of charge in the material and improve Li + The migration rate is increased, which effectively promotes the insertion and extraction process of lithium ions. The positive electrode material modified by bismuth ferrite reinforcement phase has a certain degree of improvement in discharge specific capacity, coulomb efficiency, cycle stability, rate performance, and voltage decay.
[0012] To achieve the above object, the present invention provides the following technical solutions.
[0013] A novel composite positive electrode material for a secondary battery has a traditional positive electrode material as a matrix phase and bismuth ferrite as a reinforcement phase; bismuth ferrite is combined with the traditional positive electrode material to obtain a novel composite positive electrode material.
[0014] Further optimization, the traditional positive electrode material is metal lithium oxide or metal sodium oxide.
[0015] Further optimized, the metal includes one or more of nickel, cobalt, manganese, iron, aluminum, vanadium, and titanium.
[0016] Further optimized, the metal lithium oxide is one or more of lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, lithium vanadate, lithium iron phosphate, ternary nickel cobalt manganese / lithium aluminum oxide, and lithium-rich manganese-based positive electrode materials.
[0017] Further optimized, the metal sodium oxide is one or more of sodium iron phosphate / vanadium, sodium manganate, sodium nickelate, sodium cobaltate, sodium vanadate, and sodium nickel iron manganate.
[0018] Further optimization, the mass ratio of the bismuth ferrite to the mass ratio of the traditional positive electrode material is 1-10%.
[0019] Another object of the present invention is to provide a method for preparing a new composite positive electrode material for a secondary battery, with a traditional positive electrode material as a matrix phase and bismuth ferrite as a reinforcing phase; by coating bismuth ferrite on the surface of the traditional positive electrode material in a certain way, a new composite positive electrode material can be obtained.
[0020] For further optimization, the approach includes: one or a combination of sol-gel method, co-precipitation method, mixing method (solid phase method), hydrothermal method, and spray drying method.
[0021] Compared with the prior art, the present invention has the following beneficial effects: (1) The equipment and preparation process required for preparing the material of the present invention are simple, the material is widely distributed, the cost is low, and it is environmentally friendly.
[0022] (2) The bismuth ferrite-modified positive electrode material prepared by the present invention can achieve relatively excellent electrochemical performance of the battery, and its electrochemical performance in various aspects such as discharge capacity, first-cycle coulomb efficiency, cycle stability, and rate performance has been improved to a certain extent. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to make the technical solutions involved in the embodiments of the present invention or the prior art more clear, the drawings included in the embodiments or the prior art description are briefly introduced below. It should be noted that these drawings only show some specific embodiments recorded in the present invention, and do not cover all possible implementation methods.
[0024] Figure 1 2 are the XRD patterns of Example 1 and Comparative Example 1.
[0025] Figure 2 This is a scanning electron microscope (SEM) image of Example 1.
[0026] Figure 3 This is a transmission electron microscope (TEM) image of Example 1.
[0027] Figure 4 This is the HRTEM electron microscope image of Example 1 under STEM mode.
[0028] Figure 5 is a scanning electron microscope (SEM) image of Comparative Example 1.
[0029] Figure 6 BiFeO prepared by sol-gel method 3 Scanning electron microscope image of .
[0030] Figure 7 It is a comparison diagram of the first cycle charge and discharge curves of Example 1 and Control Example 1.
[0031] Figure 8 It is a long cycle comparison diagram of Example 1 and Control Example 1 at a current density of 0.5 C.
[0032] Fig. 9 It is a long cycle comparison diagram of Example 1 and Control Example 1 at 1 C current density.
[0033] Fig.10 It is a comparison chart of the rate performance of Example 1 and Control Example 1 at different current densities. DETAILED DESCRIPTION
[0034] Next, the technical scheme of the present invention will be described in detail and comprehensively. It should be noted that the embodiments described only represent a part of the present invention and do not cover all embodiments. At the same time, all other embodiments that can be obtained by those skilled in the art without creative work based on the embodiments provided by the present invention should also belong to the protection scope of the present invention. In the following examples, unless otherwise specified, the instruments and materials used are all commercially available.
[0035] Example 1 Lithium-rich manganese-based cathode materials (Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O 2 ) as the matrix phase, bismuth ferrite as the reinforcement phase, and the bismuth ferrite-enhanced modified lithium-rich manganese-based positive electrode material is prepared by a sol-gel method. The specific steps of implementation are as follows: (1) BiFeO 3 As components, weigh 6.2030 g of Bi(NO 3 ) 3 -5H 2 O, 5.1663 gFe(NO 3 ) 3 -9H 2 O, and 24.0934 g (1.5 times the metal ion molar ratio) C 6 H 8 O 7 -H 2O was dissolved in methanol solution, and a certain amount of ethylene glycol solution was added. The solution was stirred at 500 r / min for 0.5 h to completely dissolve the solution and obtain a colloidal solution. The solution was then boiled at 85 °C at 500 r / min. After the solution evaporated, it was placed in a forced air drying oven for foaming at 130 °C for 18 h.
[0036] (2) Pour the dried gel into a mortar and grind it for 40 min to obtain the precursor powder. Then, place it in a muffle furnace and heat it to 400 °C at a rate of 2 °C / min and keep it for 1 h. Then, heat it to 550 °C at a rate of 1 °C / min and keep it for 3 h. After cooling in the furnace, grind it for 20 min to obtain BiFeO 3 Material.
[0037] (3) 0.06 g of bismuth ferrite material obtained by the sol-gel method was mixed evenly with a mixed solution of deionized water and ethylene glycol, and ultrasonicated for 30 min to obtain bismuth ferrite suspension A; 0.9045 g Ni(NO 3 ) 2 .6H 2 O, 0.8962 g Co(NO 3 ) 2 .6H 2 O, 4.5321 g Mn(NO 3)2、 2.0577 g LiNO 3 and 16.9968 g C 6 H 8 O 7 .H 2 O was dissolved in deionized water and stirred at 500 r / min for 0.5 h to obtain liquid B; then liquid A was slowly added to liquid B to obtain a ferroelectric modified suspension; the obtained suspension was stirred at 400 r / min for 15 min to mix evenly, moved to a magnetic heating stirring table and evaporated the solution at 400 r / min at 90 °C to obtain a gel, which was then placed in a 150 °C forced air drying oven and dried for 15 h to obtain a fluffy dry gel.
[0038] (4) The dry gel was poured into a mortar and ground for 30 min to obtain a finer precursor powder, which was then placed in a muffle furnace and heated to 450 °C at a rate of 2 °C / min for 6 h, then heated to 800 °C at a rate of 3 °C / min for 12 h. After cooling in the furnace, the powder was ground for 20 min to obtain the modified lithium-rich manganese-based positive electrode material Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O 2 @BiFeO 3The bismuth ferrite content in the obtained positive electrode material is 3%wt.
[0039] (5) Preparation of lithium-ion battery: The surface-modified lithium-rich manganese-based positive electrode material prepared in Example 1, acetylene black, polyvinylidene fluoride and N-methylpyrrolidone were mixed to form a slurry, which was evenly coated on the surface of an aluminum foil to obtain a positive electrode sheet. The lithium sheet was used as the negative electrode sheet, and 1 mol / L lithium hexafluorophosphate (LiF 6 )'s ethylene carbonate (EC), dimethyl carbonate (DMC) solution, and ethyl methyl carbonate (EMC) solution in a volume ratio of 1:1:1 were used as electrolyte and assembled in a glove box to obtain a lithium ion battery.
[0040] (6) The electrochemical performance of the lithium-ion battery of Example 1 was tested using a blue battery test system at a test temperature of 25°C. The initial charge and discharge performance of the battery was tested at a current density of 0.1C (1C = 250 mAh / g) and a charge and discharge voltage range of 2-4.8 V. The cycle performance at different current densities was also tested. The rate performance of the battery was tested at rates of 0.1C, 0.2C, 0.5C, 1C, 2C, and 5C.
[0041] (7) The XRD test, SEM test and TEM test characterization of the bismuth ferrite modified lithium-rich manganese-based positive electrode material prepared in this embodiment are as follows: Figure 1 , 2 , 3, and 4. Figure 1 is the XRD diagram of Example 1 and Comparative Example 1, Figure 1 It can be seen that compared with the original material, the peak intensity ratio of (003) / (104) of the lithium-rich manganese-based positive electrode material modified with bismuth ferrite is greater than the peak intensity ratio of (003) / (104) in the original material (Comparative Example 1), indicating that the modified positive electrode material reduces the degree of lithium-nickel mixing on the material surface; at the same time, the splitting of the (006) and (012) as well as the (018) and (110) peaks is consistent, indicating that the introduction of the bismuth ferrite reinforcement phase does not change the structure of the raw material.
[0042] Figure 2 , 3 , 4 are respectively the SEM morphology picture, TEM morphology picture and HRTEM characterization picture of Example 1, Figure 2 , 3 It can be seen that the particle size of the prepared lithium-rich manganese-based positive electrode material is about 0.2-0.3 μm, and the particle size of the material is relatively uniform. Through transmission electron microscopy characterization, it can be seen that the bismuth ferrite material forms a white coating layer of about 2nm on the surface of the lithium-rich manganese-based positive electrode material ( Figure 3 ); HRTEM images of materials in STEM mode are as follows Figure 4As shown, it can be clearly seen that the BiFeO3 material is evenly coated on the outer layer of the positive electrode material. Figure 6 This is an electron microscope morphology of BiFeO3 material prepared by the sol-gel method. Its particle size is about 0.1-0.3 μm and the particle size is relatively uniform.
[0043] (8) When the bismuth ferrite-enhanced and modified lithium-rich manganese-based positive electrode material prepared in this embodiment is used in lithium-ion batteries, its electrochemical properties are significantly better than those of the lithium-rich manganese-based positive electrode raw material (Comparative Example 1): In the voltage range of 2-4.8 V, the discharge capacity of the first cycle can reach 284.4 mAh / g at a rate of 0.1 C, and the first cycle coulombic efficiency is 78.1% ( Figure 7 ), the first cycle can achieve a discharge capacity of 224.8 mAh / g at a current density of 0.5 C, and the capacity retention rate after 200 cycles is 199.5 mAh / g ( Figure 8 ), the capacity retention rate is 88.74%; at 1 C current density, the first cycle can achieve a discharge capacity of 210.1 mAh / g, and after 200 cycles, the capacity retention rate is 178.13 mAh / g ( Fig. 9 ), and its capacity retention rate is as high as 84.9%. Fig.10 The figure is a rate performance test diagram of the modified (before) and after materials. The discharge specific capacity of the positive electrode material modified with bismuth ferrite is better than that of the original lithium-rich manganese-based positive electrode material at different rates, especially at higher rates and when the current density at a high rate returns to a low current density. At a high rate of 5 C, the capacity of the material prepared in this embodiment remains at 90.2 mAh / g, which is much higher than the 67.7 mAh / g of the raw material. The electrochemical performance comparison of Example 1 and Control Example 1 is shown in the following table (the bold part indicates better performance): .
[0044] Comparative Example 1 Li-rich manganese-based cathode material Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O 2 The raw materials are used as a control example, and the materials are prepared by the gel method. The specific steps are as follows: (1) Prepare the lithium-rich manganese-based positive electrode material Li according to the steps in Example 1 1.2 Ni 0.13 Co 0.13 Mn 0.54 O 2, The difference is that bismuth ferrite material does not need to be added during the preparation process, and other conditions are exactly the same.
[0045] (2) The obtained lithium-rich manganese-based positive electrode material was coated according to Example 1, assembled into button-type batteries, and then the electrochemical performance was tested.
[0046] (3) The XRD pattern of the lithium-rich manganese-based positive electrode material prepared in this comparative example is as follows: Figure 1 As shown, there is no obvious difference in phase between the material prepared in Example 1 and the particle morphology of the material is similar ( Figure 4 ).
[0047] (4) When the lithium-rich manganese-based cathode material prepared in this comparative example is used in a lithium-ion battery, the first cycle discharge capacity is 257.4 mAh / g at 0.1 C in the voltage range of 2-4.8 V, and the first cycle coulombic efficiency is 76.8% ( Figure 7 ); The first cycle discharge capacity at 0.5 C current density is 188.0 mAh / g, and the capacity retention rate after 100 cycles is 124.7 mAh / g ( Figure 8 ), the capacity retention rate is only 66.32%; the first cycle discharge capacity at 1 C current density is 175.8 mAh / g, and the capacity retention rate after 200 cycles is 50.9 mAh / g ( Fig. 9 ), the capacity retention rate is only 28.95%, and its cycle performance is much lower than that of the modified lithium-rich manganese-based positive electrode material. From the rate performance diagram ( Fig.10 ) It can be seen that the rate performance of the raw material is lower than that of the lithium-rich manganese-based positive electrode material modified with bismuth ferrite in Example 1.
[0048] Example 2 High nickel ternary cathode material (LiNi 0.8 Mn 0.1 Co 0.1 O 2 ) as the matrix phase, bismuth ferrite as the reinforcement phase, and the bismuth ferrite-enhanced modified high-nickel ternary positive electrode material is prepared by coprecipitation method. The specific steps of implementation are as follows: (1) According to the stoichiometric ratio, manganese sulfate, nickel sulfate, and cobalt sulfate were weighed in a molar ratio of 0.8:0.1:0.1 to prepare an aqueous solution with a total concentration of 2 mol / L. At the same time, a 2 mol / L sodium hydroxide solution and a 1 mol / L ammonia solution were prepared. The metal salt solution, sodium hydroxide solution, and ammonia solution were added to the reactor in parallel using a peristaltic pump. The pH was adjusted to 11 with ammonia water. The feed rate of the peristaltic pump was 500 mL / h. The water bath temperature of the reactor was controlled at 60 °C. The stirring speed during the reaction was 600 r / min. After the precipitation reaction was complete, the aging was continued for 10 h to obtain a precipitated precursor. The precipitate was filtered and washed with deionized water until no sulfate ions remained. The precursor was dried in a vacuum drying oven at 120 °C. (2) Weigh 0.02 g of bismuth ferrite, 1.8987 g of the dried precursor and 1.0979 g (5% excess) of lithium hydroxide in a mortar and mix them evenly. Place them in a magnetic boat and calcine them in a muffle furnace in an oxygen atmosphere at a heating rate of 3°C / min. Pre-calcine at 500°C for 6 h and then calcine at 850°C for 12 h. After sintering, cool naturally to room temperature and grind for 20 min to obtain BiFeO 3 Modified and enhanced cathode material LiNi 0.8 Mn 0.1 Co 0.1 O 2 @BiFeO 3 The bismuth ferrite content in the obtained positive electrode material is 1%wt.
[0049] (3) The obtained lithium-rich manganese-based positive electrode material was coated according to Example 1, assembled into button-type batteries, and then the electrochemical performance was tested.
[0050] (4) When the high nickel ternary cathode material prepared in this embodiment is used in a lithium ion battery, in the voltage range of 2.7-4.6 V, the first cycle discharge capacity at 0.1C is 208.4 mAh / g, and the first cycle coulomb efficiency is 92.6%; the first cycle discharge capacity at 0.5C current density is 190.1 mAh / g, and the capacity retention rate after 300 cycles is 170.23 mAh / g, and the capacity retention rate is 89.55%; the first cycle discharge capacity at 1C current density is 180.6 mAh / g, and the capacity retention rate after 500 cycles is 160.3 mAh / g, and the capacity retention rate is 88.75%.
[0051] Comparative Example 2 High nickel ternary cathode material (LiNi 0.8 Mn 0.1 Co 0.1 O 2 ) Raw materials are used as control examples, and the materials are prepared by coprecipitation method. The specific steps are as follows: (1) Prepare high nickel ternary positive electrode material LiNi according to the steps in Example 2 0.8 Mn 0.1 Co 0.1 O 2 The only difference is that bismuth ferrite material does not need to be added during the preparation process, and other conditions are exactly the same.
[0052] (2) The obtained positive electrode material was coated according to Example 1, assembled into button-type batteries, and then the electrochemical performance was tested.
[0053] (3) When the high nickel ternary cathode material prepared in this embodiment is used in a lithium ion battery, in the voltage range of 2.7-4.6 V, the first cycle discharge capacity at 0.1C is 202.4 mAh / g, and the first cycle coulomb efficiency is 90.6%; the first cycle discharge capacity at 0.5C current density is 181.13 mAh / g, and the capacity retention rate after 300 cycles is 137.87 mAh / g, and the capacity retention rate is 76.11%; the first cycle discharge capacity at 1C current density is 172.4 mAh / g, and the capacity retention rate after 500 cycles is 115.7 mAh / g, and the capacity retention rate is 67.11%.
[0054] Example 3 The lithium iron phosphate / lithium cobalt oxide / ternary nickel cobalt manganese oxide (nickel: cobalt: manganese = 6:2:2) purchased on the market is used as the matrix phase (mass ratio is 1:1:1), and bismuth ferrite is used as the reinforcement phase. The new cathode material modified by bismuth ferrite as the reinforcement phase is prepared by a solid phase method (mixing method). The specific steps of implementation are as follows: (1) Weigh 2 g each of commercial cathode materials, lithium iron phosphate, lithium cobalt oxide, and lithium nickel cobalt manganese oxide, and weigh 0.6 g of bismuth ferrite, and put them into a small planetary ball mill in the laboratory for 10 h. Then, put the mixed powder into a muffle furnace and heat it to 650 °C at 3 °C / min for 5 h. After cooling in the furnace, grind for 20 min to obtain BiFeO 3 The modified and enhanced positive electrode material has a bismuth ferrite content of 10%wt.
[0055] (2) The obtained positive electrode material was coated according to Example 1, assembled into button-type batteries, and then the electrochemical performance was tested.
[0056] (3) When the modified positive electrode material prepared in this embodiment is used in a lithium ion battery, in the voltage range of 2.7-4.5 V, the first cycle discharge capacity at 0.1 C is 170.4 mAh / g, the first cycle coulomb efficiency is 90.6%, the first cycle discharge capacity at 0.5 C current density is 160.1 mAh / g, the capacity after 300 cycles is 148.3 mAh / g, and the capacity retention rate is 92.62%; the first cycle discharge capacity at 1 C current density is 153.6 mAh / g, the capacity retention rate after 500 cycles is 140.3 mAh / g, and the capacity retention rate is 91.34%.
[0057] Comparative Example 3 The raw materials (mass ratio of 1:1:1) of lithium iron phosphate / lithium cobalt oxide / ternary nickel cobalt manganese oxide (nickel: cobalt: manganese = 6:2:2) purchased from the market were used as a control example, and the material was prepared by a solid phase method. The specific steps are as follows: (1) The material was prepared according to the steps in Example 3, except that bismuth ferrite material was not required to be added during the preparation process, and the other conditions were completely the same.
[0058] (2) The obtained positive electrode material was coated according to Example 1, assembled into button-type batteries, and then the electrochemical performance was tested.
[0059] (3) When the novel cathode material prepared in this embodiment is used in a lithium-ion battery, in the voltage range of 2.7-4.5 V, the first cycle discharge capacity at 0.1 C is 162.4 mAh / g, and the first cycle coulombic efficiency is 88.6%; the first cycle discharge capacity at 0.5 C current density is 152.44 mAh / g, and the capacity retention rate after 300 cycles is 113.65 mAh / g, and the capacity retention rate is 74.55%; the first cycle discharge capacity at 1 C current density is 146.9 mAh / g, and the capacity retention rate after 500 cycles is 107.54 mAh / g, and the capacity retention rate is 73.21%.
[0060] Example 4 Sodium nickel iron manganese oxide positive electrode material (NaNi 0.7 Fe 0.2 Mn 0.1 O 2 ) as the matrix phase, bismuth ferrite as the reinforcement phase, and the bismuth ferrite-enhanced modified sodium nickel iron manganese oxide positive electrode material is prepared by a hydrothermal method. The specific steps of implementation are as follows: (1) According to the stoichiometric ratio of 7:2:1, weigh appropriate amounts of nickel acetate, iron acetate and manganese acetate and dissolve them in 50 mL of deionized water, and stir them thoroughly to dissolve them. Weigh 20 mmol of sodium hydroxide powder and dissolve it in 40 mL of deionized water to fully dissolve it. Add 2 ml of ammonia water as a complexing agent, and add a certain amount of PVP surfactant to it, and then mix it thoroughly by ultrasonication. Then stir the prepared solution in a nitrogen atmosphere for 30 minutes, and put the mixed solution into a reactor for hydrothermal reaction. After the hydrothermal reaction is completed, place the precipitated product in a drying oven at 180 ° C and fully dry it to obtain the precursor Ni 0.7 Fe 0.2 Mn 0.1 (OH) 2 ; (2) Weigh 1.6280 g of the obtained precursor Ni 0.7 Fe 0.2 Mn 0.1 (OH) 2 , 0.9493 g Na 2 CO 3and 0.1 g of bismuth ferrite material obtained by the sol-gel method were mixed evenly by a ball mill, heated to 500 °C at a rate of 2 °C / min in an oxygen atmosphere and kept for 5 h, then heated to 800 °C at a rate of 3 °C / min and kept for 10 h, cooled in the furnace and ground for 20 min to obtain NaNi 0.7 Fe 0.2 Mn 0.1 O 2@ BiFeO 3 Positive electrode material, the content of bismuth ferrite in the obtained positive electrode material is 5%wt.
[0061] (3) The modified positive electrode material was coated and assembled into button-type batteries according to Example 1, and then the electrochemical performance was tested.
[0062] (4) When the positive electrode material prepared in this embodiment is used in a sodium ion battery, in the voltage range of 2.5-4.2 V, the first cycle discharge capacity at 0.1 C is 140.4 mAh / g, the first cycle coulomb efficiency is 85.6%, the first cycle discharge capacity at 0.5 C current density is 110.1 mAh / g, and the capacity retention rate after 200 cycles is 90.23 mAh / g, and the capacity retention rate is 81.95%; the first cycle discharge capacity at 1 C current density is 91.6 mAh / g, and the capacity retention rate after 200 cycles is 76.3 mAh / g, and the capacity retention rate is 83.29%.
[0063] Comparative Example 4 Sodium nickel iron manganese oxide positive electrode material (NaNi 0.7 Fe 0.2 Mn 0.1 O 2 ) Raw materials are used as control examples, and the materials are prepared by hydrothermal method. The specific steps are as follows: (1) Prepare the sodium nickel iron manganese oxide positive electrode material NaNi according to the steps in Example 4 0.7 Fe 0.2 Mn 0.1 O 2 The only difference is that bismuth ferrite material does not need to be added during the preparation process, and other conditions are exactly the same.
[0064] (2) The obtained positive electrode material was coated according to Example 1, assembled into button-type batteries, and then the electrochemical performance was tested.
[0065] (3) When the high nickel ternary cathode material prepared in this embodiment is used in a lithium ion battery, in the voltage range of 2.5-4.2 V, the first cycle discharge capacity at 0.1C is 133.6 mAh / g, and the first cycle coulomb efficiency is 83.2%; the first cycle discharge capacity at 0.5C current density is 101.25 mAh / g, and the capacity retention rate after 200 cycles is 57.12 mAh / g, and the capacity retention rate is 56.41%; the first cycle discharge capacity at 1C current density is 76.3 mAh / g, and the capacity retention rate after 200 cycles is 39.91 mAh / g, and the capacity retention rate is 52.31%.
[0066] Example 5 Lithium iron phosphate (LiFePO 4 ) as the matrix phase, bismuth ferrite as the reinforcement phase, and the bismuth ferrite-enhanced modified lithium iron phosphate positive electrode material is prepared by spray drying. The specific steps of implementation are as follows: (1) Weigh 10 g of commercially available lithium iron phosphate cathode material and add 500 mL of deionized water to disperse it into suspension A; take 0.4 g of bismuth ferrite prepared by the sol-gel method and disperse it in 50 mL of deionized water to obtain suspension B; then transfer liquid B to liquid A and stir thoroughly to obtain a mixed suspension C; (2) adding the suspension obtained by sufficient stirring into a laboratory small spray dryer and drying it to obtain a precursor powder; (3) The powder was placed in a muffle furnace and heated to 700 °C at a heating rate of 3 °C / min and kept at that temperature for 8 h. After cooling in the furnace, a bismuth ferrite-enhanced lithium iron phosphate positive electrode material was obtained, in which bismuth ferrite accounted for 4%wt of the mass of the positive electrode material.
[0067] (4) The obtained modified lithium iron phosphate positive electrode material was coated according to Example 1, assembled into button-type batteries, and then the electrochemical performance was tested.
[0068] (5) When the lithium iron phosphate positive electrode material prepared in this embodiment is used in a lithium ion battery, in the voltage range of 2.5-4.2 V, the first cycle discharge capacity at 0.1 C is 147.4 mAh / g, the first cycle coulomb efficiency is 92.6%, the first cycle discharge capacity at 0.5 C current density is 135.1 mAh / g, and the capacity retention rate after 500 cycles is 115.6 mAh / g, and the capacity retention rate is 85.56%; the first cycle discharge capacity at 1 C current density is 116.6 mAh / g, and the capacity retention rate after 500 cycles is 97.3 mAh / g, and the capacity retention rate is 83.45%.
[0069] Comparative Example 5 Lithium iron phosphate (LiFePO 4) Raw materials are used as control examples, and the materials are prepared by spray drying. The specific steps are as follows: (1) Treat lithium iron phosphate LiFePO according to the steps in Example 5 4 The raw materials are different in that bismuth ferrite material does not need to be added during the preparation process, and other conditions are exactly the same.
[0070] (2) The obtained positive electrode material was coated according to Example 1, assembled into button-type batteries, and then the electrochemical performance was tested.
[0071] (3) When the lithium iron phosphate cathode material prepared in this embodiment is used in a lithium ion battery, in the voltage range of 2.5-4.2 V, the first cycle discharge capacity at 0.1C is 143.6 mAh / g, and the first cycle coulomb efficiency is 90.7%; the first cycle discharge capacity at 0.5C current density is 130.77 mAh / g, and the capacity retention rate after 500 cycles is 95.44 mAh / g, and the capacity retention rate is 72.98%; the first cycle discharge capacity at 1C current density is 105.3 mAh / g, and the capacity retention rate after 200 cycles is 73.91 mAh / g, and the capacity retention rate is 70.19%.
[0072] In summary, we have prepared modified positive electrode materials with a variety of positive electrode materials as the matrix and bismuth ferrite as the reinforcing phase through various preparation methods. The electrochemical properties of the modified positive electrode materials have been greatly improved in all aspects, which provides a good solution for improving battery performance.
[0073] The technical solution of the present invention is not limited to the above-mentioned specific implementation cases. Any technical deformation, modification, substitution and variation made according to the technical solution of the present invention without departing from the purpose of the present invention and the protection scope of the claims shall fall within the protection scope of the present invention.
Claims
1. A novel composite positive electrode material for a secondary battery, characterized in that: The traditional positive electrode material is used as the matrix phase and bismuth ferrite is used as the reinforcement phase; bismuth ferrite is combined with the traditional positive electrode material to obtain a new composite positive electrode material.
2. The novel composite positive electrode material for a secondary battery according to claim 1, characterized in that: The conventional positive electrode material is metal lithium oxide or metal sodium oxide.
3. The novel composite positive electrode material for a secondary battery according to claim 2, characterized in that: The metal includes one or more of nickel, cobalt, manganese, iron, aluminum, vanadium and titanium.
4. The novel composite positive electrode material for a secondary battery according to claim 2, characterized in that: The metal lithium oxide is one or more of lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, lithium vanadate, lithium iron phosphate, ternary nickel cobalt manganese / lithium aluminum oxide, and lithium-rich manganese-based positive electrode materials.
5. The novel composite positive electrode material for a secondary battery according to claim 2, characterized in that: The metal sodium oxide is one or more of sodium iron phosphate / vanadium, sodium manganate, sodium nickelate, sodium cobaltate, sodium vanadate, and sodium nickel iron manganate.
6. The method for enhancing the electrochemical performance of a secondary battery positive electrode material using bismuth ferrite as an auxiliary material according to claim 1, characterized in that: The mass ratio of the bismuth ferrite to the mass ratio of the traditional positive electrode material is 1-10%.
7. The method for preparing the novel composite positive electrode material for secondary batteries according to any one of claims 1 to 6, characterized in that: The traditional positive electrode material is used as the matrix phase and bismuth ferrite is used as the reinforcement phase; bismuth ferrite is coated on the surface of the traditional positive electrode material in a certain way to obtain a new composite positive electrode material.
8. The method for enhancing the electrochemical performance of a secondary battery positive electrode material using bismuth ferrite as an auxiliary material according to claim 7, characterized in that: The approaches include: one or a combination of sol-gel method, coprecipitation method, mixing method (solid phase method), hydrothermal method, and spray drying method.
Citation Information
Patent Citations
Preparation method of molybdenum trioxide cladded lithium-rich manganese-based positive electrode material
CN109509874A
Composition and preparation method thereof
CN107946563A
Preparation method of silicon-carbon composite negative electrode material
CN112164773A
Secondary battery positive electrode including ferroelectric component and method of manufacturing same
CN114551875A
Ferroelectric modified positive electrode material, preparation method thereof and secondary battery
CN115939403A